Judges Beyond politics in democracy and dictatorship. Lessons from Chile by Lisa Hisa Hilbink - Benito, Ana Belén (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2008)
Review of Judges Beyond politics in democracy and dictatorship. Lessons from Chile